HUBUNGAN PENGGUNAAN MEDIA PEMBELAJARAN DENGAN MINAT BELAJAR SISWA PADA MATA PELAJARAN FIQIH KELAS IV MI AL MADANI TAJUR HALANG KAB. BOGOR - Silmi Siti Rabiatul Adawiyah; Muhammad Fahri (Attadib: Journal of Elementary Education, 2018)
This study aims to (1) know the use of audiovisual learning media in the subjects of Fiqh class IV in MI Al-Madani, (2) to know students' interest in the subject of Fiqh class IV in MI-Al-Madani, (3) to know the relationship of usage media learning with interest in student learning subject of Fiqh class IV in MI Al-Madani. In this study using correlation method, this correlation method is part of quantitative research with field research type (field research). In this study the researchers used a sample of all populations of 95 students. Instruments used in this study are: observation, questionnaires, and documentation. Based on data analysis, the research result can be concluded that: (1) it can be seen that the use of learning media in the subject of Fiqh class IV in MI Al-Madani got the interpretation of good enough value with the average respondent answer SL "Always" of 47.36% (2) it can be seen that the interest of student learning on the subject of Fiqh class IV in MI Al Madani gets the interpretation of good enough value with the average respondent answer the category SL "Always" of 51.68% (3) there is a moderate correlation low between the use of learning media with students' interest in the subjects of fiqh in grade IV MI Al-Madani. It can be seen based on interpretation table of rxy value data is 0,240 is between 0,20-0,40 and can be seen by comparing the amount of rxy with rt that rxy (0,240) while "rt" each significance level 5% (0,195) and 1% significance level (0.254) means 0.240> 0.195 and 0.240 <0.254. Thus, rxy (0.240) is greater than "rt" at a significant level of 5% (0.195), then at a significant level of 5% Alternative Hypothesis (Ha) is accepted while the Nil Hypothesis (Ho) is rejected. Then at a significant level of rxy (0.240) smaller than a significant level of 1% (0.254), the Alternative Hypothesis (Ha) is rejected while the Nil Hypothesis (Ho) is accepted or approved. This means that for the level of significance of 1% there is no significant positive correlation between variable X and variable Y. Because at the level of 5% rxy greater than rt, the conclusion that can be taken is there is a significant relationship between the use of learning media with student learning interests on the subject of Fiqh class IV in MI Al-Madani Tajur Halang Bogor District.